RESPON PERTUMBUHAN BEBERAPA VARIETAS PADI SETELAH REMEDIASI TANAH YANG TERDAMPAK LIMBAH TAMBANG - Muh Basyaruddin; Marlina Mustafa; Mustafa Mustafa; Muhammad Al Afandi (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2026)
This study aims to determine the growth response of several rice varieties on land remediated due to nickel mining waste impacts, as well as to identify the variety with the best growth and production. The research was conducted at the experimental field of the Faculty of Agriculture, Fisheries, and Animal Husbandry, University of SembilanBelas November Kolaka, from July to October 2025. The research method used a Randomized Block Design (RBD) with treatments consisting of five rice varieties: MR, Birma, IPB 9 G, Inpari 42, and IPB 15 S, with three replications. Soil remediation was carried out through the application of biochar and a phytoremediation system before use as a growing medium. The observed parameters included plant height, number of tillers, leaf area, and leaf color. Analysis of variance showed that varieties had a highly significant effect on plant height, but no significant effect on the number of tillers, leaf area, and leaf color. The Birma variety produced the highest average plant height (96.17 cm) and was significantly different from other varieties, while the MR variety showed the lowest growth (65.33 cm). The results indicate that the remediation process was able to maintain soil condition stability although it was still in the acidic category. In general, the application of biochar and phytoremediation was able to support the vegetative growth of rice plants on mining waste-affected land. The Birma variety is recommended as the most adaptive and potential variety to be developed on post-mining land